Women's empowerment within the tourism industry - Bayram, Gul Erkol; Shah, Syed Haider Ali; Tunio, Muhammad Nawaz 1984- (IGI Global, 2023)
Boivin, Jacquelynne Anne
Keywords: Women in tourism; Women in the hospitality industry